Building digital resilience: leading healthcare transformation through an online community - Pilosof, Nirit Putievsky; Welcman, Yaara; Barrett, Michael; Oborn, Eivor; Barrett, Stephen (Frontiers in Digital Health, 2025)
IntroductionHealthcare systems globally face systemic vulnerabilities, such as crisis response, insufficient capacity, lack of integration, and rising care costs while simultaneously being pressured to accelerate the shift toward digital health solutions. In response, new organizational forms and digitally enabled collaborations have emerged to support care continuity and innovation. This study examines how digital resilience can be built at a system level through a national online community of healthcare professionals. Drawing on a longitudinal qualitative case study of Israel's Digital Health Community, an initiative launched by the Ministry of Health in 2020 in response to COVID-19 crisis, we explore how a digitally mediated, cross-sectoral online community with more than 1,200 medical professionals from various disciplines and organizations enabled national healthcare transformation through digital resilience.MethodsUsing interviews, observations, and digital document analysis conducted over four years, we trace how the online community enabled systemic resilience through three interconnected dynamics: the redefinition of roles and responsibilities across disciplines, enhanced collaboration across organizations and governance levels, and the development of a culture of innovation.ResultsBy challenging existing norms, the online community facilitated an entrepreneurship approach, fostering leadership in healthcare transformation and overcoming professional resistance to change. These interactions helped generate integrated models of care, informed national digital health regulation, and enabled rapid experimentation in service design and delivery. We argue that digital resilience plays an important role in enabling these healthcare transformations.DiscussionWe present a conceptual model that illustrates how digital resilience is produced not as a fixed organizational trait, but as an emergent, multi-level outcome of structured community engagement. It highlights the need for new governance models that merge top-down and bottom-up involvement and leadership, moving from hierarchical to network structures to diffuse innovation and transformation among diverse stakeholders across the healthcare ecosystem.ConclusionsOur findings contribute to the growing literature on digital health transformation by highlighting the role of participatory, networked approaches to resilience-building. The study offers actionable insights for policymakers and health system leaders seeking to institutionalize adaptive capacity through digitally enabled collaboration.